Effect of different abiotic factors on symptom expression and severity of bakanae disease of rice (Oryza sativa) - YADAV, JAGDISH; BASHYAL, B M; SINHA, PARIMAL; AGGARWAL, RASHMI (The Indian Journal of Agricultural Sciences, 2020)
The bakanae disease incited by Fusarium fujikuroi Nirenberg is becoming a serious threat to cultivation of rice, especially aromatic rice worldwide. The present study was conducted in the year 2016–17 at ICAR- Indian Agricultural Research Institute, New Delhi to study the effect of different abiotic factors (soil moisture, soil pH, soil type, and temperature) individually and in combination in causation of different kind of bakanae disease symptoms and severity. The highest disease severity (93.33%) was observed at 30% soil moisture conditions. Variation in disease severity was significant in interaction of moisture and soil type and temperature and soil type, whereas, it was non-significant in interaction of moisture and temperature and soil type, moisture and temperature. It was observed that elongation symptoms were more prevalent in high moisture conditions, whereas rotting symptoms were more prevalent in low soil moisture.